Mid-infrared optical coherence tomography and machine learning for inspection of 3D-printed ceramics at the micron scale - Heise, Bettina; Zorin, Ivan; Duswald, Kristina; Karl, Verena; Brouczek, Dominik; Eichelseder, Julia; Schwentenwein, Martin (Frontiers in Materials, 2024)
Introduction In this paper, recent developments in non-destructive testing of 3D-printed ceramics and monitoring of additive manufacturing of ceramics are presented. Methods In particular, we present the design and use of an inline mid-infrared optical coherence tomography (MIR-OCT) system to evaluate printed and micro-structured specimens in lithography-based ceramic manufacturing (LCM). Results The proposed system helps with the detection of microdefects (e.g., voids, inclusions, deformations) that are already present in green ceramic components, thereby reducing the energy and costs incurred. Discussion The challenges during integration are discussed. Especially, the prospects for MIR-OCT imaging combined with machine learning are illustrated with regard to inline inspection during LCM of printed ceramics.